UTVRĐIVANJE EFIKASNOSTI TURISTIČKOG SEKTORA POJEDINIH EVROPSKIH DRŽAVA I REGIONA PRIMENOM DEA ANALIZE - Pavković, Vladimir; Jević, Goran; Jević, Jelena; Nguyen, Phong Thanh; Sava, Cipriana (Journal of process management and new technologies, 2021)
Abstract: The paper presents research results of efficiency of tourism sector in certain European countries and regions obtained by applying DEA method. The primary goal of the paper is to determine to what extent tourism sector in certain European countries and regions is efficient in relation to set parameters, while the secondary goal is aimed at providing recommendations for its improvement. In relation to this, the methodology of the DEA analysis is based on the input and output parameters which were used to determine the efficiency. The input parameters included: number of hotels and similar accommodation capacities, number of rooms and number of bed places, whereas the output parameters included: number of inbound tourists, number of bed-nights and tourism expenditure during their stay abroad. One of the conclusions of the paper is that the total efficiency was shown in Croatia, Belgium, and Denmark, while the technical efficiency was also present in North Macedonia, France, Malta, the Netherlands, Portugal, and Spain.